STRATEGI NEPAL MENINGKATKAN DAYA SAING CHYANGRA PASHMINA DI PASAR GLOBAL TAHUN 2016-2021 - Nadilla, Paperia; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Nepal is a landlocked country in the South Asian region that has abundant resources and beautiful scenery. One of the natural products that has the potential to become an export product is chyangra pashmina. This pashmina is made from the finest wool of the stomach and neck hair of the Himalayan goat which is commonly called chyangra. This goat fiber is claimed to be “Diamond Fiber” and “Soft Gold of High Asia” because it has very soft, light and smooth fibers so that Nepalese Pashmina is considered a luxury item. However, this success did not last long because India and China, which are Nepal’s main competitors, flooded the market with pashmina which had low prices and quality. This makes the high quality Nepalese Pashmina lose its image. Seeing this situation, the government of Nepal took steps to restore Nepal’s pashmina image and increase its competitiveness in the global market by making relevant policies through Nepal Trade Integration Strategy (NTIS) 2016. In this qualitative research using data collection techniques that come from books, journals, theses, official documents, reports and websites that have relevance to research. This study also uses a mercantilism perspective with the level of nation-state analysis, as well as the theory of comparative advantage and the concept of national interest. The results of this study indicate the strategy of the Nepalese government to increase the competitiveness of chyangra pashmina in the global market which can be grouped into 3 aspects, namely: 1) improving quality and market in line with the development of the chyangra pashmina trademark; 2) improving human resources through various training related to management and skills; 3) increasing facilities and cooperation with other parties through increasing the number of chyangra goat farms and entering into trade investment aggrements. Keywords: Chyangra Pashmina, Comparative Advantage, Global Market, Strategy